A High Protein Diet Has No Harmful Effects: A One-Year Crossover Study in Resistance-Trained Males. (11th October 2016) - Antonio, Jose; Ellerbroek, Anya; Silver, Tobin; Vargas, Leonel; Tamayo, Armando; Buehn, Richard; Peacock, Corey A.
Abstract : The purpose of this investigation was to determine the effects of a high protein diet over a one-year period. Fourteen healthy resistance-trained men completed the study (mean ± SD; age26.3 ± 3.9  yr; height178.5 ± 8.4  cm; and average years of training8.9 ± 3.4  yr). In a randomized crossover design, subjects consumed their habitual or normal diet for 2 months and 4 months and alternated that with a higher protein diet (>3 g/kg/d) for 2 months and 4 months. Thus, on average, each subject was on their normal diet for 6 months and a higher protein diet for 6 months. Body composition was assessed via the Bod Pod® . Each subject provided approximately 100–168 daily dietary self-reports. During the subjects' normal eating phase, they consumed (mean ± SD)29.94 ± 5.65  kcals/kg/day and2.51 ± 0.69  g/kg/day of protein. This significantly increased (p < 0.05 ) during the high protein phase to34.37 ± 5.88  kcals/kg/day and3.32 ± 0.87  g/kg/day of protein. Our investigation discovered that, in resistance-trained men that consumed a high protein diet (~2.51–3.32 g/kg/d) for one year, there were no harmful effects on measures of blood lipids as well as liver and kidney function. In addition, despite the total increase in energy intake during the high protein phase, subjects did not experience an increase in fat mass.